PENGARUH PAJAK, UKURAN PERUSAHAAN, PROFITABILITAS DAN LEVERAGE TERHADAP KEPUTUSAN PERUSAHAAN UNTUK MELAKUKAN TRANSFER - Helti Cledy; Muhammad Nuryatno Amin (Jurnal Akuntansi Trisakti, 2020)
This study aims to determine the effect of tax, company size, profitability, and leverage on the company's decision to practice transfer pricing. The dependent variable in this study is transfer pricing. Meanwhile, the independent variables used are tax, company size, profitability, and leverage. The study was conducted on manufacturing companies listed on the Indonesia Stock Exchange (IDX) with a purposive sampling method. The sample used was 31 companies with an observation period of 3 years, so as many as 93 samples were obtained. The data of this study were obtained by looking at the company's financial statements in the period 2016-2018. This study used logistic regression analysis with SPSS ProgramThe results showed that tax and profitability had a positive effect on the company's decision to transfer pricing. While company size and leverage variables do not affect the company's decision to transfer pricing